2023
DOI: 10.1002/tcr.202300031
|View full text |Cite
|
Sign up to set email alerts
|

19F‐Labeled Probes for Recognition‐Enabled Chromatographic 19F NMR

Abstract: The NMR technique is among the most powerful analytical methods for molecular structural elucidation, process monitoring, and mechanistic investigations; however, the direct analysis of complex real‐world samples is often hampered by crowded NMR spectra that are difficult to interpret. The combination of fluorine chemistry and supramolecular interactions leads to a unique detection method named recognition‐enabled chromatographic (REC) 19F NMR, where interactions between analytes and 19F‐labeled probes are tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…Previously, we delved deep into understanding the dynamic recognition properties of various synthetic receptors, aiming to achieve precise multicomponent chemosensing. 48,49 In this context, metal complexes that possess bound ligands that can be replaced by incoming analytes are frequently utilized. By using a suitable chiral scaffold, enantiomeric analytes can exert distinct influences on the strategically positioned 19 F labels on the probe, leading to effective chiral discrimination.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previously, we delved deep into understanding the dynamic recognition properties of various synthetic receptors, aiming to achieve precise multicomponent chemosensing. 48,49 In this context, metal complexes that possess bound ligands that can be replaced by incoming analytes are frequently utilized. By using a suitable chiral scaffold, enantiomeric analytes can exert distinct influences on the strategically positioned 19 F labels on the probe, leading to effective chiral discrimination.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A recent progress in chemical sensing via 19 F NMR offers a promising solution to the traditional challenges of using NMR for complex mixture analysis. , Given its 100% natural abundance and the absence of organofluorine compounds in nature, 19 F proves to be an optimal nucleus for creating a highly sensitive and interference-free detection system. By leveraging the sensitivity of the 19 F chemical shift to its local environment, ingeniously designed probes can detect analytes and produce distinct 19 F NMR signals for each analyte in a complex mixture. This method, often referred to as recognition-enabled chromatographic 19 F NMR, is especially effective when the interaction between the 19 F-labeled probe and the analytes is reversible, producing a chromatogram-like output. It has been successfully applied to detect alcohols, amides, amines, N-heterocycles, and even allows for chiral discrimination. , In 2014, Swager and colleagues crafted 19 F-labeled calix[4]­arene tungsten-imido complexes as molecular hosts for recognizing nitrile compounds . These host structures can encapsulate analytes, generating a unique “fingerprint” for identifying nitrile analytes (Scheme a) .…”
Section: Introductionmentioning
confidence: 99%
“…10 This approach combines the benefits of operational simplicity and ease of spectrum interpretation, which is often referred to as recognition-enabled chromatographic 19 F NMR. 11 Although this method has been applied to the detection of various chiral substances, demonstrating a broader scope than derivatization-based methods, few investigations have focused on strategies to tune the resolving ability of the 19 F-labeled probe. Previously, we demonstrated that altering the metal center and constructing Lewis acid–base pairs can enhance the performance of chiral discrimination systems.…”
mentioning
confidence: 99%
“…It's important to mention that for analytes where enantiomers exhibit different binding strengths towards the 19 F-labeled probe, a correction coefficient can be applied to account for the unequal binding affinity. 11,12 Our previous studies have shown that incorporating this correction coefficient allows for accurate determination of the enantiocomposition. The results achieved with this adjusted method showed an average absolute deviation of less than 2% compared to HPLC analysis, underscoring the reliability of this approach in enantiomeric analysis.…”
mentioning
confidence: 99%